Memorable Tourist Experience, Perceived Value, and Storytelling in Elopement Weddings at Tibumana Waterfall - Ni Made Putri Sherin Natalia; I Putu Utama; Ni Made Eka Mahadewi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study investigates the effect of memorable tourist experiences on storytelling behavior in elopement weddings at Tibumana Waterfall, with perceived value examined as a mediating variable. The research aims to test the hypotheses that memorable tourist experiences positively influence storytelling behavior and that perceived value enhances this relationship. A purposive sampling technique was applied to 140 respondents consisting of couples who had conducted elopement weddings at the destination. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with a two-stage approach. The findings reveal that memorable tourist experiences significantly and positively affect storytelling behavior, while perceived value functions as a complementary mediator, strengthening this relationship. These results highlight the importance of designing wedding experiences that maximize perceived value to stimulate post-visit storytelling. The study contributes to the theoretical development of memorable tourist experience research and offers practical implications for destination branding and marketing strategies, particularly in promoting elopement weddings through authentic visitor storytelling.